Predictors of moderate to severe fatigue 12 months following admission to hospital for burn: Results from the Burns Registry of Australia and New Zealand (BRANZ) Long Term Outcomes project. Issue 8 (December 2016) - Gabbe, Belinda J.; Cleland, Heather; Watterson, Dina; Schrale, Rebecca; McRae, Sally; Taggart, Susan; Darton, Anne; Wood, Fiona; Edgar, Dale W.; ,
Highlights: Fatigue is a common after burn but is rarely measured in outcome studies. Moderate to severe fatigue was prevalent in the first 12-months after burn. Patients with fatigue had poorer health-related quality of life. Patients with fatigue experienced higher work-related disability. Gender, geographic remoteness and burn size were predictors of fatigue. Abstract: Introduction: Fatigue has been identified as an outcome of concern following burn but is rarely captured in outcomes studies. We aimed to: (i) describe the prevalence, and predictors, of moderate to severe fatigue in the first 12 months following burn, and (ii) establish the association between fatigue and health-related quality of life and work outcomes. Methods: Adult burns patients, admitted >24 h, were recruited from five BRANZ sites. Participants were followed-up at 1-, 6-, and 12-months after injury using the Brief Fatigue Inventory (BFI), 36-item Short Form Health Survey (SF-36) and the Sickness Impact Profile (SIP)—work scale. Moderate to severe fatigue was defined as a global BFI score of 4–10. Multivariable mixed effects regression modelling was used to identify demographic, socioeconomic, burn size and severity predictors of moderate/severe fatigue at follow-up. Results: The mean ± SD age of the 328 participants was 42.1 ± 16.7 years, 70% were male, 47% were flame burns, and the mean ± SD %TBSA was 8.7 ± 11.2. The prevalence of moderate/severe fatigue decreased from 37% at 1-month, to 32% at 6-months and 26% at 12-months. The adjusted odds of moderate/severe fatigue were 2.62 (95% CI: 1.27, 5.42) times higher for women compared to men, and 2.64 (95% CI: 1.03, 6.79) times higher in patients with a %TBSA ≥ 20. Compared to patients in major cities, the adjusted odds of reporting moderate/severe fatigue were 2.48 fold higher (95% CI: 1.17, 5.24) for patients residing in inner regional areas, and 3.60 fold (95% CI: 1.43, 9.05) higher for patients living in remote/very remote areas. At each time point, the physical and mental health summary scores, and each sub-scale score, of the SF-36 were significantly lower in patients reporting moderate/severe fatigue. Patients experiencing moderate to severe fatigue reported higher work-related disability on the SIP work scale at each time point after injury. Discussion and conclusion: More than a quarter of participants reported moderate to severe fatigue on the BFI at 12-months and fatigue was strongly associated with poorer health-related quality of life and greater work-related disability.